Jilidan Indonesian Journal of Clinical Pathology and Medical Laboratory: Majalah Patology Klinik Indonesia dan Laboratorium Medik Vol 22 no 1-3 2015 - Redaksi (Perhimp Dok Sp Patologi Klinik, 2015)
Jilidan Indonesian Journal of Clinical Pathology and Medical Laboratory: Majalah Patology Klinik Indonesia dan Laboratorium Medik